Pro-Peace vs. Pro-War Conceptualizations in the Language of Hungarian Propaganda - Marcin Grygiel (Research in Language)
The language of propaganda can be treated as a specialist language with its own specialized terminology. It is produced by groups of variously configured propaganda experts responsible for the creation of propaganda messages, placed at one end of the communication channel, together with its specific target audience that consumes these messages, situated at the other end of the communication channel. As a result of this specialized communication process, the language of propaganda is function-oriented and its focus is always put on the objectives that are to be achieved. These include shaping and manipulating public opinions. For these goals to be successful, the language of propaganda must be equipped with efficient and well-designed conceptualizations able to change and modify the way people think. Defined as such, the language of propaganda is not a purely linguistic construct, but a multimodal tool able to make use of the visual and audiovisual output as well. The interest in mental processes such as conceptualization lies at the very center of cognitive linguistics and the study of cognitive mechanisms responsible for various types of conceptualizations is of high priority in cognitively driven approaches to language. Another issue which makes cognitive linguistics suitable for this type of research in specialist languages is its long standing preference for multidisciplinary and multimodal phenomena. Applying the methodology of cognitive linguistics, the present paper aims at identifying and discussing the PRO-PEACE vs. PRO-WAR network of conceptualizations in the language of Hungarian propaganda, often compared in its mastery with Orwell’s newspeak or the Soviet propaganda machinery because of its power and influence. Hungary’s leading right-wing party, Fidesz-KDNP, has retained political control in Hungary ever since its landslide victory in the 2010 national elections and developed a powerful propaganda tool that is ideally customized to the culture-specific preferences of Hungarian voters. Through quantitative and qualitative analysis, this research studies linguistic expressions shaping PRO-PEACE vs. PRO-WAR conceptualizations with their rich social, historical and cultural contexts.